INDUSTRIAL ACCOUNTING INSTRUCTION AND THE NATIONAL-DEFENSE PROGRAM. - Garner, S. Paul (The Accounting Review, 1942)
Abstract The article presents information about the industrial accounting courses that are being conducted in the U.S. as a part of the Engineering, Science, and Management Defense Training Program (better known as ESMDT). The U.S. Congress inaugurated this program in July 1941. It may be observed that the ESMDT program is in reality just an expansion of the university extension adult education programs, which have been set up by many institutions in the years past. The program involves a definite innovation, however, in that the Federal government hitherto has limited its financial assistance to vocational level courses. Several educational authorities have expressed certain misgivings as to the implications underlying this move. It is felt by some that the ESMDT represents a type of Federally sponsored higher education which may have permanent and wide repercussions even after the present war is over. Little attention has been given to this important matter up to the present time, as the national and local administrators have been too busy with problems involved in setting up the institutional programs to deal adequately with the long-term aspects of this type of adult education. As the program gains headway over the next few months, more thought will naturally have to be devoted to the relative permanency of the organization, and also to its coordination with the now existing extension activities of the universities and colleges of the country.